Pengembangan LKPD Mini Booklet Kearifan Lokal Pada Pembelajaran Bahasa IndonesiaKelas V SD - Vanesa Dwi Agustin; Nurul Istiq’faroh; Ledia Hanifah; Adzra Taqiyah Zahra Labibah (CV. Kurnia Grup, 2026)
Indonesian language learning in elementary schools is often monotonous and teacher-centered, leading to low reading interest and comprehension among students, with minimal integration of local wisdom to enrich cultural literacy. Local wisdom constitutes knowledge, values, and traditions that develop within society and are passed down from generation to generation as part of a region’s cultural identity. Through learning based on local wisdom, students not only acquire academic knowledge but also learn to know, understand, and appreciate their own regional culture. This study aimed to develop a Mini Booklet LKPD based on Solo City’s local wisdom to enhance reading skills for fifth-grade elementary students. The Research and Development (R&D) method using the 4D model (Define, Design, Develop, Disseminate) was implemented at an elementary school in Gresik during the even semester of 2025/2026, involving needs analysis, design, expert validation, and trials with 23 students. Instruments included validation sheets and response questionnaires, analyzed descriptively and quantitatively. Results indicated the LKPD was highly feasible (media expert 80%, material expert 88%) and practical (77.75%). In conclusion, this LKPD serves as an innovative, engaging, and contextual medium; future prospects include testing its effectiveness on learning outcomes and expansion to other materials.